1981
DOI: 10.1017/s0003356100040630
|View full text |Cite
|
Sign up to set email alerts
|

The effects of concentrate supplements on the performance of dairy cows offered grass silage ad libitum

Abstract: Ninety-six lactating British Friesian cows were offered ad libitum two grass silages having the following analyses: 181 and 241 g dry matter per kg fresh weight, 108 and 96g digestible crude protein per kg dry matter and 617 and 619 g digestible organic matter per kg dry matter. In addition, four concentrate supplements were offered, containing either 360 g crude protein per kg on an air-dry basis and given at the rate of 015 kg/kg milk or 180 g crude protein per kg given at the rate of 030, 0375 and 0·45 kg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…However, this effect is sometimes observed in early lactation, as in the current experiment, and is likely due to low energy status in cows on a pure forage diet (Laird et al, 1981;Aston et al, 1995). The unsupplemented cows lost weight and were in negative energy balance (Table 7).…”
Section: Milk Production and Compositionmentioning
confidence: 65%
“…However, this effect is sometimes observed in early lactation, as in the current experiment, and is likely due to low energy status in cows on a pure forage diet (Laird et al, 1981;Aston et al, 1995). The unsupplemented cows lost weight and were in negative energy balance (Table 7).…”
Section: Milk Production and Compositionmentioning
confidence: 65%
“…Schmidt and Van Vleck (1974), that the lactose content of the milk is unaltered by the feeding regime, several experiments have shown a positive correlation between the level ofenergy intake and the milk lactose content (e.g. Rook and Storry, 1964;Laird et at., 1981).…”
Section: Animat Productionmentioning
confidence: 99%
“…In the data from our field trial and in those reported by Laird et al (1981) and Moisey and Leaver (1985) the coefficients for the dependent variable (MP) in regressions (1) and (4) were 4-11 and 4-38 respectively. When these are rounded up to 4-0 it can be assumed that if deviations of MP from the supposed norm of 0-31 are reduced by a factor of 0-25, MP will have equal weighting with BCS.…”
mentioning
confidence: 48%
“…It is calculated that in the experiment of Laird et al (1981) the range was -14-5 to +5-0 and in that of, Moisey and Leaver (1985) with higher milk yields and fixed levels of feeding ('flat-rate feeding') the range was +5-5 to +12-5. It is calculated that in the experiment of Laird et al (1981) the range was -14-5 to +5-0 and in that of, Moisey and Leaver (1985) with higher milk yields and fixed levels of feeding ('flat-rate feeding') the range was +5-5 to +12-5.…”
mentioning
confidence: 98%
See 1 more Smart Citation